The geopolitical orientations of ordinary Belarusians: survey evidence from early 2020. Issue 1 (4th March 2022) - O'Loughlin, John; Toal, Gerard
ABSTRACT: Examining geopolitical orientations in a representative survey of Belarus in early 2020, we adopt a critical geopolitical perspective that highlights geopolitical cultures as fields of contestation and debate over a state's identity, orientation, and enduring interests. We examine support among 1210 Belarusians to four foreign policy options for the country – neutrality as the best foreign policy, joining the European Union, staying in the Eurasian Economic Union, or developing close relations with both these organizations. We also analyze responses to where Belarus should be on an 11-point scale from aligned with the West to aligned with Russia. In early 2020, Belarusians indicated divided geopolitical preferences in the same way as other post-Soviet societies along demographic, ideological, and attitudinal cleavages. Lukashenka's quarter-century dictatorship has left Belarus in a condition of nascent (geo)political polarization. The 2020 electoral crisis alone did not polarize Belarus; it was already a dividing polity.